"Their Fingers Were too Fat to Weave": Ancient Textiles and Academic Politics Today. (October 2014) - Soffer, Olga; Adovasio, J. M.
In 1993, we recognized textile impressions on fragments of fired clay from Upper Paleolithic sites in Moravia, which documented the world's oldest weaving, net making, and basketry. We published this discovery first in Czech in their premier professional journal and in collaboration with Moravian colleagues. Subsequently, this evidence was augmented by new data from across Eurasia, the recognition of textile products on the "Venus" figurines, and the identification of tools used to make them. Our discovery received a bifurcate reception. While scholars outside of the Czech Republic accepted it readily, local academics split into feuding factions. Below we discuss the evidence for Paleolithic textiles and use its reception to illustrate that: 1) the deep past necessarily lives in the political present, and 2) the present is contested and multi-vocal. Our article also serves to raise the questions of whose voice to privilege, and why.